EVALUASI KARAKTER PEKA PANJANG HARI (PHOTOPERIOD) PADA TIGA GOLONGAN (Subspecies) PADI (Oryza sativa) SERTA PENGARUHNYA TERHADAP KARAKTER AGRONOMIS - Tintin Suhartini (BERITA BIOLOGI, 2009)
Day length or photoperiod is a situation of replacement of light period to dark which able to control the flower initiation and also growth of crop. Rice is short day plant; if day length exceed the critical phase it will be late of flowering.The purpose of this experiment was to evaluate rice cultivars which differ in groups and agronomic characters to photoperiod.The experiment was done at two seasons in November 1997 and May 1998 at green house BB-BIOGEN Bogor. The total of 29 cultivars consist of 3 subspesies of javanica, indica and japonica type were used. The experiment was based on randomized block design with 4 replications. The result showed the local varieties were sensitive and javanica were medium, while improved varieties and japonica type were insensitive to photoperiod. The effect of seasons were significantly different to flowering days of local and javanica types, significantly and not significantly different to japonica, while not significantly different to improved varieties. The season has not significant effect to panicle length and unfilled grain per panicle characters for all cultivars type. Plant heigth and dry straw per hill were higher in rainy season, while fill grain per panicle, total grain per panicle and 1000 grain weight were higher in dry season. The results showed there have correlation between flowering days to all characters were observed, except number of tiller in rainy season was not correlated.